Expression of cytokeratin confers multiple drug resistance. - Bauman, P A (1994)
The cytokeratin network is an extensive filamentous structure in the cytoplasm whose biological function(s) is unknown. Based upon previous data showing the modification of cytokeratin by mitoxantrone, we investigated the ability of cytokeratin networks to influence the survival response of cells to chemotherapeutic agents. We have compared the survival of mouse L fibroblasts lacking cytokeratins with that of L cells transfected with cytokeratins 8 and 18 in the presence of chemotherapeutic drugs. The expression of cytokeratins 8 and 18 conferred a multiple drug resistance phenotype on cells exposed to mitoxantrone, doxorubicin, methotrexate, melphalan, Colcemid, and vincristine. The degree of drug resistance was 5-454 times that of parental cells, depending upon the agent used. Drug resistance could not be attributed to altered growth characteristics, altered drug accumulation, or an altered drug efflux in the transfected cells. Cytokeratin does not confer resistance to ionizing radiation, which damages DNA independently of intracellular transport mechanisms. These data suggest a role for cytokeratin networks in conferring a drug resistance phenotype.